In Vitro Assessment of Antifungal Caspofungin on Leishmania donovani Culture Isolation - Narayan Raj Bhattarai; Keshav Rai; Suman Rijal; Basudha Khanal (Canadian Journal of Infectious Diseases and Medical Microbiology)
Leishmania parasite isolation from the human aspirates is always challenging due to most probability of the fungal contamination and the use of antifungal drug which could support the selective growth of the Leishmania parasite. In this study, we examine the effect of antifungal drug caspofungin on the promastigote stage of Leishmania donovani. Promastigote parasite was cultivated in M199 + 20% heat-inactivated fetal calf serum and plated in 96-well plates. Seven different concentrations of caspofungin (512 µg/ml to 8 µg/ml) were exposed to parasites, and 50% inhibitory concentration (IC50) was calculated. Candida spp. was used in the experiments to know the efficacy of caspofungin to inhibit fungal growth. The IC50 values of Leishmania strains ranged from 23.02 to 155.80 µg/ml (mean 90.25 ± 39.01 µg/ml), and it was significantly higher (P value = 0.02) than IC50 values of Candida spp. (ranged from 0.001 to 0.12 µg/ml, mean = 0.05 ± 0.05 µg/ml). The reduced growth rate of the parasite was found with exposure to 50 µg/ml of caspofungin. Growth inhibition of Leishmania donovani is significantly lower with caspofungin and could be used to protect the parasite cultivation from fungal contamination.